2023
DOI: 10.1001/jamaophthalmol.2023.2271
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Artificial Intelligence in Estimating Best-Corrected Visual Acuity From Fundus Photographs in Eyes With Diabetic Macular Edema

Abstract: ImportanceBest-corrected visual acuity (BCVA) is a measure used to manage diabetic macular edema (DME), sometimes suggesting development of DME or consideration of initiating, repeating, withholding, or resuming treatment with anti–vascular endothelial growth factor. Using artificial intelligence (AI) to estimate BCVA from fundus images could help clinicians manage DME by reducing the personnel needed for refraction, the time presently required for assessing BCVA, or even the number of office visits if imaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, the most important goal of DME treatment is to maximize the maintenance and protection of the patient's vision. Previous studies have shown that diabetes can lead to retinal ischemia and hypoxia in patients, promote the growth of vascular endothelial growth factor (VEGF) and then increase the permeability of the vascular wall, as well as induce neovascularization, thereby leading to the damage of the inner and outer retinal barrier, and the occurrence of DME [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most important goal of DME treatment is to maximize the maintenance and protection of the patient's vision. Previous studies have shown that diabetes can lead to retinal ischemia and hypoxia in patients, promote the growth of vascular endothelial growth factor (VEGF) and then increase the permeability of the vascular wall, as well as induce neovascularization, thereby leading to the damage of the inner and outer retinal barrier, and the occurrence of DME [12].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with growing awareness of these technologies is increasingly nuanced knowledge regarding potential limitations and considerations for clinical implementation. In this issue of JAMA Ophthalmology , Paul et al describe the development of an AI algorithm for estimating best-corrected visual acuity (BCVA) from color fundus photographs among eyes with diabetic macular edema (DME) using data from the VISTA clinical trial that compared efficacy and safety of intravitreal aflibercept injection vs macular laser photocoagulation for DME over 3 years. The rationale is to potentially decrease the need for manual refraction and visual acuity measurement that can often be time-consuming and effort intensive.…”
mentioning
confidence: 99%
“…The AI algorithms described in this study tended to perform worse among patients with poorer visual acuities. The authors hypothesized that this may have been due to a relatively small number of eyes with poorer visual acuities represented in the training data. AI algorithms, especially deep-learning algorithms like the ones used in this particular study, are data hungry and often require large amounts of training data to achieve high performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations